Effect of Different In Vitro Aging Methods on Color Stability of a Dental Resin‐Based Composite Using CIELAB and CIEDE2000 Color‐Difference Formulas. Issue 5 (1st June 2015) - de Oliveira, Dayane Carvalho Ramos Salles; Ayres, Ana Paula Almeida; Rocha, Mateus Garcia; Giannini, Marcelo; Puppin Rontani, Regina Maria; Ferracane, Jack L.; Sinhoreti, Mario Alexandre Coelho; Paravina, Rade
Abstract Purpose To evaluate the effect of different in vitro aging methods on color change (CC) of an experimental dental resin‐based composite using CIELAB (ΔEab) and CIEDE2000 (ΔE00) color‐difference formulas. Materials and Methods The CC was evaluated with a spectrophotometer (CM700d, Konica Minolta, Tokyo, Japan) according to the CIE chromatic space. Disk‐shaped specimens (Φ = 5 × 1 mm thick) (N = 10) were submitted to different in vitro aging methods: 30 days of water aging (WA); 120 hours of ultraviolet light aging (UVA); or 300 hours of an accelerated artificial aging (AAA) method with cycles of 4 hours of UV‐B light exposure and 4 hours of moisture condensation to induce CC. The temperature was standardized at 37°C for all aging methods. CC was evaluated with ΔEab and ΔE00 formulas. Differences in individual Lab coordinates were also calculated. Data for the individual color parameters were submitted to one‐way analysis of variance and Tukey's test for multiple comparisons (α = 0.05). Results All in vitro aging methods tested induced CC, in the following order: WA: ΔEab= 0.83 (0.1); ΔE00 = 1.15 (0.1) < AAA: ΔEab = 5.64 (0.2); ΔE00 = 5.01 (0.1) < UVA: ΔEab = 6.74 (0.2); ΔE00 = 6.03 (0.4). No changes in L* or a* coordinates were ≥1; the methods with UV aging showed a yellowing effect due a large positive change in b*. Conclusions All in vitro aging methods tested induced a CC, but to different extents. Changes in color followed similar trends, but with different absolute values when calculated with the CIELAB and the CIEDE2000 formulas. Clinical Significance Establishing the efficacy of different artificial aging methods and differences between color change using CIELAB and CIEDE2000 formulas are important to standardize color stability evaluations and facilitate the comparison of outcomes from different studies in the literature.